PENGARUH KEPEMIMPINAN KEUCHIK TERHADAP EFEKTIFITAS PELAYANAN MASYARAKAT GAMPONG KAMBUEK PAYAPI KUNYET KECAMATAN PADANG TIJI - Halimah Halimah; Anwar Anwar; Ricky Muliawan Hansyar; Munawir Munawir (Jurnal Sosial Humaniora Sigli, 2023)
Effectiveness is a very important element of organizational activities in achievingpredetermined goals or objectives. When viewed from the aspect of the success of achieving goals, effectiveness is focusing on the level of achievement of organizational goals. Furthermore, in terms of timeliness, effectiveness is the achievement of various goals that have been determined on time by using certain references that have been allocated to carry out various activities. Community Service is one of the main things that must be considered by a Keuchik / village head in leading the progress of the village in the future. Assessment of the influence of leadership on the effectiveness of services to the people of Gampong Kambuek Payapi Kunyet, Padang Tiji District was carried out by conducting direct interviews with the people of Gampong Kambuek Payapi Kunyet, Padang Tiji District. The research sampling was carried out by purposive sampling, which means that not all populations were sampled. The number of respondents sampled as a whole amounted to 137 people. Primary data is obtained by interviewing respondents and using a list of questions that have been prepared on a questionnaire. Analysis of the assessment of the influence of leadership on the effectiveness of services to the people of Gampong Kambuek Payapi Kunyet, Padang Tiji District is carried out on the effectiveness of services in the field ofcorrespondence, in the field of infrastructure development, in the field of Islamic law enforcement, and in the field of dispute resolution. From the results of the interview, it was found that the influence of the leadership of the village head on the effectiveness of community services in Gampong Kambuek Payapi Kunyet, Padang Tiji District is in the field of correspondence services, the majority of the community rated it as good (70%), inthe field of infrastructure development services, the majority of the community rated it as very good (31%), in the field of Islamic sharia implementation services, the majority of the  community rated it as quite good (33%), and in the field of dispute resolution services, the majority of the community rated it as good (35%).Keywords: Influence, Leadership, Village Head, Effectiveness of Community Services